2003
DOI: 10.1046/j.1523-1747.2003.12550_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity and Mutation Spectrum in Hypotrichosis with Juvenile Macular Dystrophy

Abstract: Hypotrichosis with juvenile macular dystrophy is a rare autosomal recessive disorder characterized by abnormal growth of scalp hair during infancy, and by the later occurrence of macular degeneration leading to blindness during the first to third decade of life. Hypotrichosis with juvenile macular dystrophy was recently shown to result from mutations in CDH3 encoding P-cadherin. In this study, we assessed 27 individuals, including nine patients, belonging to five families in an attempt to characterize further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 13 publications
3
60
1
Order By: Relevance
“…This is an autosomal recessive disorder mainly characterized by hair loss and progressive macular degeneration leading to early blindness (52). The R503H mutation results in a single histidinefor-arginine substitution at position 503 (26,27), which is part of the highly conserved Ca 2+ -binding LDRE motif in the EC4 repeat of P-cadherin. As shown in cadherins related to P-cadherin, the LDRE motif is crucial for the proper folding of the extracellular domain of the cadherin molecule, enabling stable cis and trans cadherin interactions (25,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an autosomal recessive disorder mainly characterized by hair loss and progressive macular degeneration leading to early blindness (52). The R503H mutation results in a single histidinefor-arginine substitution at position 503 (26,27), which is part of the highly conserved Ca 2+ -binding LDRE motif in the EC4 repeat of P-cadherin. As shown in cadherins related to P-cadherin, the LDRE motif is crucial for the proper folding of the extracellular domain of the cadherin molecule, enabling stable cis and trans cadherin interactions (25,53).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter P-cadherin mutant, we mimicked the R503H mutation found in congenital hypotrichosis with juvenile macular dystrophy (HJMD) patients (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, previous reports have demonstrated that the identical mutation 829delG resulted in HJMD in one family (Indelman et al, 2003), while it led to EEM syndrome in another family (Kjaer et al, 2005), which suggests that an identical mutation can give rise to different phenotypes between families (Fig. 9).…”
Section: Research Articlementioning
confidence: 91%
“…9). Nevertheless, in HJMD families, all affected individuals have hair and eye involvement only (Sprecher et al, 2001;Indelman et al, 2002;Indelman et al, 2003;Indelman et al, 2005;Indelman et al, 2007). Similarly, in EEM families, all affected individuals show not only hair and eye phenotype but also hand/foot involvement (Kjaer et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation